PENGARUH CITRA MEREK DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK NIPPON PADA TOKO BANGUNAN SURYA JAYA MANDIRI LEBAK BANTEN - Suriah Suriah; Ali Mubarok (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Environment on Employee Performance at PT Pesat Servis Industri in South Tangerang, both partially and simultaneously. The research method used is a quantitative method. The population in this study were all employees of PT Pesat Servis Industri South Tangerang, totaling 60 respondents with a sample of 60 respondents. Data analysis techniques used data instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests. The results showed that Work Experience had a significant effect on Employee Performance with the regression equation Y = 10.654 + 0.741 X1, the correlation coefficient value was 0.772, the determination coefficient had a contribution of 57.9%, and the hypothesis test obtained t count> t table (9.239> 2.002) which means H01 was rejected and Ha1 was accepted. The work environment significantly influences employee performance, with the regression equation Y = 6.211 + 0.892 X2, a correlation coefficient of 0.851, a coefficient of determination contributing 72.4%, and a hypothesis test showing a calculated t-value > t-table (12.338 > 2.002), indicating that H02 is rejected and Ha2 is accepted. Work experience and work environment significantly influence employee performance, with the regression equation Y = 2.570 + 0.338 X1 + 0.637 X2, a correlation coefficient of 0.888, a coefficient of determination contributing 78.9%, and a hypothesis test showing a calculated F-value > F-table (106.472 > 3.16), indicating that H03 is rejected and Ha3 is accepted.